Developing entrepreneurial career intention in entrepreneurial university: the role of counterfactual thinking. Issue 5 (4th May 2022) - Karim, Mohammed Shamsul; Sena, Vania; Hart, Mark
ABSTRACT: This study addressed the question of how the counterfactual thinking of a student in an entrepreneurial university affects his/her future entrepreneurial career intention. In addition to testing this relationship, we also test how counterfactual thinking moderates the influence of attitude and opportunity identification in entrepreneurial career intention in an entrepreneurial university. We found that in an entrepreneurial university, counterfactual thinking is modifying the influence of attitude and opportunity identification in entrepreneurial career intention, but counterfactual thinking has no significant direct influence on entrepreneurial career intention of the students.